Pediatric nasal dermoid sinus cysts: advances in pathogenesis, management strategies, and translational research—a multidisciplinary management perspective - Quan, Shan; He, Li; Geng, Jiangqiao; Wang, Juan (Frontiers in Pediatrics, 2026)
BackgroundPediatric nasal dermoid/sinus cysts (NDSC) are common congenital midline craniofacial lesions associated with embryonic tissue entrapment and abnormal midline fusion during embryogenesis; they can involve intracranial structures and predispose patients to recurrent infection, intracranial complications, and cosmetic or functional impairment, posing challenges for diagnosis, treatment, and long-term management.ObjectiveTo review the pathogenesis, diagnostic and therapeutic strategies, and advances in clinical translation of NDSC, and to explore optimization of care under multidisciplinary management.MethodsWe systematically reviewed recent literature on embryology, imaging, surgical techniques, and multidisciplinary team (MDT) approaches.ResultsAberrant midline fusion and ectodermal inclusion during embryogenesis represent the principal pathogenic theories; lesions may be classified as superficial, sinus-tract, or those with intracranial extension. MRI is the imaging modality of choice, CT is used for osseous assessment, and ultrasound and endoscopy serve as bedside and intraoperative adjuncts. Treatment centers on complete excision: external rhinoplasty approaches, endoscopic endonasal techniques, or combined intracranial–extracranial approaches should be individualized according to imaging-based classification; perioperative infection control and standardized follow-up substantially reduce recurrence. In clinical translation, intraoperative navigation, radiomics, and MDT collaboration have improved operative safety and cosmetic outcomes, whereas studies addressing molecular mechanisms, biomarkers, and long-term functional prognosis remain insufficient.ConclusionWe recommend implementing individualized surgical strategies guided by imaging classification and advancing MDT decision pathways; future work should intensify molecular and radiomics research to achieve more precise diagnosis, therapeutic selection, and long-term prognostic assessment.